Acute spontaneous compartment syndrome in recent onset type 1 diabetes. - Mahdi, H; Gough, S; Gill, K; Mahon, B (2007)
Acute spontaneous compartment syndrome is a rare orthopaedic emergency that usually presents to general physicians as an acute medical admission. Most cases reported to date, in patients with diabetes, are in those with long-standing disease or with evidence of diabetic complications. An acute spontaneous compartment syndrome in a girl with recent diagnosis of type 1 diabetes is reported here. Awareness of the condition allows early recognition and diagnosis, thereby preventing more severe muscle necrosis and disability.